2014
DOI: 10.1176/appi.neuropsych.12110287
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Neuropsychological Safety of Subgenual Cingulate Gyrus Deep Brain Stimulation for Treatment-Resistant Depression

Abstract: Deep brain stimulation (DBS) of the subgenual cingulate gyrus (SCG) is a promising investigational intervention for treatment-resistant depression (TRD), but long-term outcome data are limited. Serial neuropsychological evaluations, using a comprehensive battery, were conducted on four subjects with TRD prior to surgery, and up to 42 months post-operatively. Reliable change methodology suggested general stability and/or select statistically reliable improvement in cognitive abilities over time. This is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The subgenual cingulate gyrus is also one of the most effective targets in deep brain stimulation studies of treatment-resistant depression. [48][49][50] In our study, a decrease in the volume of the subgenual cingulate gyrus before treatment indicates a poorer clinical outcome after ECT. One possible explanation could be that, instead of normalizing the gray matter structure, successful treatment might result in a relative normalization of the connectivity pattern of the subgenual cingulate gyrus to other limbic areas, which in turn might require a less impaired subgenual cingulate structure.…”
Section: Discussionmentioning
confidence: 91%
“…The subgenual cingulate gyrus is also one of the most effective targets in deep brain stimulation studies of treatment-resistant depression. [48][49][50] In our study, a decrease in the volume of the subgenual cingulate gyrus before treatment indicates a poorer clinical outcome after ECT. One possible explanation could be that, instead of normalizing the gray matter structure, successful treatment might result in a relative normalization of the connectivity pattern of the subgenual cingulate gyrus to other limbic areas, which in turn might require a less impaired subgenual cingulate structure.…”
Section: Discussionmentioning
confidence: 91%
“…Previous works have also reported no neuropsychological impairment after SCG chronic stimulation and others have even found improvements in memory (Moreines et al, 2014;Bogod et al, 2014) and in frontal skills (Holtzheimer and Mayberg, 2011). In particular, Moreines and colleagues reported long-term immediate recall improvements, though without controlling for practice effects.…”
Section: Discussionmentioning
confidence: 90%
“…One of them is the subgenual cingulate gyrus (SCG), which has yielded an average of 68% of response and 44% of remission rates in five different studies (Anderson et al, 2012). To date, some of these previous studies have also investigated the cognitive effects of DBS for TRD, reporting cognitive safety of the nucleus accumbens (Grubert et al, 2011) andSCG stimulation (McNeely et al, 2008;Holtzheimer et al, 2012;Bogod et al, 2014;Moreines et al, 2014). However, these previously cited studies did not have a control group, and, if they did (Moreines et al, 2014), it was not followed over time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Boccard et al [27] demonstrated significant improvement in the affective component of chronic pain in a series of 16 patients suffering from chronic neuropathic pain. Bogod et al [28] targeted the subgenual cingulate gyrus in 4 patients with treatment-resistant depression and were able to demonstrate improved cognitive abilities using serial neuropsychological evaluations. Taken together, this body of literature leads to the conclusion that anterior cingulate cortical cells play an important role in mediating many of the higher cortical responses to pain [17,26].…”
Section: Discussionmentioning
confidence: 99%